Prognostic role of tumor size in childhood cancer. (December 2009) - Favini, Francesca; Sultan, Iyad; Meazza, Cristina; Casanova, Michela; Ferrari, Andrea
Identifying prognostic factors that influence outcome is a key point in pediatric oncology, as it enables risk stratification and helps us to fine-tune risk-adapted treatments, thereby hopefully improving the chances of survival for high-risk patients, and minimizing the burden of treatment for those whose outlook is good. Along with other clinical and biological variables, tumor size at onset has been identified as a crucial variable in several pediatric malignancies, and in soft-tissue sarcomas in particular. This review provides a critical reappraisal of the prognostic role of tumor size in pediatric soft-tissue sarcomas.